Operating IR Emitters using Internet Based Teleoperation - M.Anto Bennet, Dr.; ., Sudhagar; Saran, S.; Srikanth, R.; Rahul Bhardwaj, K. (International Journal of Engineering and Technology, 2018)
As we all know that we are slowly moving toward automation and automation is one of the trending topics. So, basically in this design we will be operating the IR emitter using internet based teleoperation. The system will get commands from the raspberry pi and it will control the IR transmitter, according to the input values, set by the user. In this design raspberry pi forms the processing part, which firstly receive the input values from the Wi-Fi connected device and sends it to the IR emitter which emits IR radiation. It is absorbed by a metal (i.e. thermometer) and gets heated. If the melting point of the metal is satisfied, by using a driver element (i.e. resistor), it is maintained constantly. We can change the input values from the Wi-Fi connected device according to the type of metal used.Â Â